2004
DOI: 10.1080/09638280410001696700
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors related to employment outcome following traumatic brain injury: a critical review and conceptual model

Abstract: A conceptual model is presented which emphasises the importance of metacognitive, emotional and social environment factors for improving employment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
193
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(202 citation statements)
references
References 96 publications
(266 reference statements)
4
193
2
3
Order By: Relevance
“…Executive functioning emerged as the most commonly cited predictor variable of RTW post TBI and was cited in three studies [23,34,35]. The Disability Rating Scale (DRS) outcome, which rates the cognitive ability to perform self-care activities, was identified as a predictor Table 2 Evidence summary Normal range scores on most neuropsychologic tests predicted a 40% to 130% increase in the probability of employment.…”
Section: Cognitive Variables Predict Return To Work Post Traumatic Brmentioning
confidence: 99%
See 2 more Smart Citations
“…Executive functioning emerged as the most commonly cited predictor variable of RTW post TBI and was cited in three studies [23,34,35]. The Disability Rating Scale (DRS) outcome, which rates the cognitive ability to perform self-care activities, was identified as a predictor Table 2 Evidence summary Normal range scores on most neuropsychologic tests predicted a 40% to 130% increase in the probability of employment.…”
Section: Cognitive Variables Predict Return To Work Post Traumatic Brmentioning
confidence: 99%
“…Ten studies identified either single or multiple cognitive variables as predictors of RTW post TBI, including 4 Level I studies [22,25,33,34], one Level II study [23], 2 Level III studies [21,26], and 3 Level IV studies [24,35,36]. Executive functioning emerged as the most commonly cited predictor variable of RTW post TBI and was cited in three studies [23,34,35].…”
Section: Cognitive Variables Predict Return To Work Post Traumatic Brmentioning
confidence: 99%
See 1 more Smart Citation
“…Survivors of TBI may fail to return to work or to maintain meaningful social relationships as a result of these changes (Brooks et al, 1987;Kendall & Terry, 1996, Malia et al, 1995Ownsworth & McKenna, 2004). For relatives of patients with TBI, the behavioral changes can be a greater burden than the physical or cognitive impairments (Brooks et al, 1986;Kinsella et al, 1991), even many years after the injury (Koskinen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment has been linked to deficiencies in self-initiated, proactive problem solving in a sample of adults diagnosed with schizophrenia [62]. Individuals with psychiatric disorders tend to use more passive coping styles compared with nondisabled controls [63][64], perhaps because of cognitive impairment. Direct assistance and guidance through the steps of initiation of help-seeking behavior and participation in treatment may then be most important for individuals with SMI and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%